Pengaruh Jumlah Penduduk, Jumlah Penyerapan Tenaga Kerja Dan Pengangguran Terhadap Jumlah Penduduk Miskin Di Kabupaten Buleleng - Wiradyatmika, A. A Gde Alit; Sudiana, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
Poorness become constraint in economics of society, because enough bother economics aktifitas. This poorness trigger some of society to do mobilization of countryside to town and town to countryside to get work. With existence of mobilization is amount of resident in town will increase and poorness in town will mount, while work field in countryside will be unifinished, because left by most its resident which go abroad to town to look for work. If this situation continue to take place, hence situation of  urban will become very solid, what later will induce at increasing unemployment storey level it town. This research aim to to know influence of[is amount of labour amount and resident and also unemployment to amount of poorness in Sub-Province of Buleleng simultaneously and parsial. Method analyse data used to solve problem in this research is multiple linear regression analysis by using program aid of SPSS Windows for. Result of research indicate that the amount of absorbtion of labour have an effect on negativity to amount of impecunious resident, while amount of unemployment have an effect on positive to impecunious resident [in] Sub-Province of Buleleng, but the amount of resident do not have an effect on signifikan to amount of impecunious resident. Matter this means amount of absorbtion of labour tend to to lessen the amount of impecunious resident, while amount of unemployment tend to to improve the amount of impecunious resident in Sub-Province of Buleleng.
Keywords: poorness; unemployment; labour